Sosialisasi Kesiapsiagaan Bencana pada Keluarga sebagai Upaya Mengurangi Dampak Risiko berbasis Digitalisasi - Sri Lestari; Yuliaji Siswanto; Kartika Dian Pertiwi (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2023)
Disaster problems in Indonesia are a special concern for the government, both central and regional. One of the areas in Semarang Regency that was affected by the disaster and has not recovered until now is Kalongan Village in East Ungaran District which was hit by a landslide in February 2022 which caused damage to the main road infrastructure connecting Ungaran-Mranggen. Even though it did not cause any casualties, this disaster had an impact on national health development from the health, resilience, environmental and socio-economic aspects. Disaster management is very important in preventing loss of life. One element of disaster management is preparedness as an action to increase life safety when a disaster occurs, especially children as the most vulnerable group. This community service activity is carried out through Disaster Preparedness Socialization to Families as an Effort to Reduce the Impact of Disaster Risk based on Digitalization. The media used in the outreach were animated videos targeting students in grades 1-3 of elementary school and disaster preparedness games for students in grades 4-5 of elementary school, a total of 132 students. Before the activity took place, students were given 10 questions as indicators of measuring knowledge before education (pretest) and after education (posttest). The results of the activity showed that there was an increase in students' knowledge in the good knowledge category as many as 61 students (46.2%). Exposure to media or sources of information, namely health promotion that is right on target, regarding disaster preparedness and emergency response with the right media can increase students' knowledge. The use of videos has been effective in increasing knowledge in the community, because in the current era videos can be played back and viewed. returned by anyone and at any time. ABSTRAK Permasalahan bencana di Indonesia menjadi salah satu perhatian khusus bagi pemerintah, baik pusat maupun daerah. Salah satu wilayah di Kabupaten Semarang yang terdampak bencana dan belum pulih hingga sekarang yaitu Desa Kalongan di Kecamatan Ungaran Timur yang terkena bencana longsor pada bulan Februari 2022 yang menyebabkan rusaknya infrastruktur jalan penghubung utama Ungaran-Mranggen. Meskipun tidak menimbulkan korban jiwa, tetapi kejadian bencana tersebut berdampak pada pembangunan kesehatan nasional baik dari aspek kesehatan, ketahanan, lingkungan maupun sosial ekonomi. Penanggulangan bencana sangat penting dalam mencegah jatuhnya korban jiwa. Salah satu unsur penanggulangan bencana adalah kesiapsiagaan sebagai tindakan untuk meningkatkan keselamatan jiwa pada saat terjadi bencana, terutama anak-anak sebagai kelompok yang paling rentan. Kegiatan pengabdian kepada masyarakat ini dilaksanakan melalui Sosialisasi Kesiapsiagaan Bencana pada Keluarga sebagai Upaya Mengurangi Dampak Risiko Bencana berbasis Digitalisasi. Media yang digunakan dalam sosialisasi adalah video animasi dengan sasaran siswa kelas 1-3 SD dan games siaga bencana untuk siswa kelas 4-5 SD sejumlah 132 siswa. Sebelum kegiatan berlangsung, siswa diberikan 10 pertanyan sebagai indicator pengukuran pengetahuan sebelum edukasi (pretest) dan sesudah edukasi (posttest). Hasil kegiatan menunjukkan terdapat peningkatan pengetahuan siswa dengan kategori pengetahuan baik sebanyak 61 siswa (46,2%). Paparan  media  atau  sumber  informasi  yaitu  promosi  kesehatan  yang  tepat sasaran,  mengenai kesiapsiagaan dan atanggap darurat bencana dengan media yang tepat dapat  membuat pengetahuan  pada siswa bertambah Penggunaan video sudah efektif dalam meningkatkan pengetahuan pada masyarakat, dikarenakan di era saat ini video bisa dibawa diputar ulang dan dilihat kembali oleh siapa saja dan kapan saja.